PENGEMBANGAN PROFESIONALISME GURU MELALUI PROGRAM PENDIDIKAN DAN PELATIHAN BERKELANJUTAN DI MADRASAH - Rudin, Elsiana (UNISAN JURNAL, 2025)
This study aims to analyze the effectiveness of continuous education and training programs in enhancing teacher professionalism in madrasahs. Teacher professionalism is a key factor in determining the quality of learning; therefore, systematic efforts are required to ensure that teachers continuously improve their knowledge, skills, and professional attitudes. This research employs a descriptive qualitative approach, utilizing observation, in-depth interviews, and documentation as data collection techniques. The findings indicate that continuous training programs have a positive impact on improving teachers’ pedagogical, professional, social, and technological competencies. Structured training activities—such as workshops, seminars, supervision, and professional learning communities—provide opportunities for teachers to learn, collaborate, and apply newly acquired knowledge in classroom practice. Additionally, strong leadership support, a collaborative school culture, and adequate facilities are major factors contributing to the success of the training programs. However, several challenges remain, including limited time, budget constraints, and the lack of professional trainers. Overall, this study concludes that continuous education and training programs are effective strategies for enhancing teacher professionalism and should be further developed as an essential component of improving the quality of education in madrasahs.